An Air Knife–Assisted Recrystallization Method for Ambient‐Process Planar Perovskite Solar Cells and Its Dim‐Light Harvesting - Cheng, Rui; Chung, Chih‐Chun; Zhang, Hong; Zhou, Zhiwen; Zhai, Peng; Huang, Yu‐Ting; Lee, Hyeonseok; Feng, Shien‐Ping (Small (Weinheim an der Bergstrasse, Germany), 2019)
The photovoltaic performance of perovskite solar cells is highly dependent on the control of morphology and crystallization of perovskite film, which usually requires a controlled atmosphere. Therefore, fully ambient fabrication is a desired technology for the development of perovskite solar cells toward real production. Here, an air‐knife assisted recrystallization method is reported, based on a simple bath‐immersion to prepare high‐quality perovskite absorbers. The resulted film shows a strong crystallinity with pure domains and low trap‐state density, which contribute to the device performance and stability. The proposed method can operate in a wide process window, such as variable relative humidity and bath‐immersion conditions, demonstrating a power conversion efficiency over 19% and 27% under 1 sun and 500–2000 lux dim‐light illumination respectively, which is among the highest performance of ambient‐process perovskite solar cells. An air knife–assisted recrystallization method is developed to fabricate high‐quality perovskite film in air under daily variable weather. The presented method is a root fabrication based on a bath‐immersion process, offering useful insights for fabricating highly efficient ambient‐process perovskite solar cells toward real production and paves a way for dim‐light harvesting and recycling.